Efeito neurodegenerativos causados pela deficiência de vitamina B1 - Fernando Augusto de Oliveira Ribeiro (2006)
Oxidative stress, selective neuronal loss, and diminished activity of thiaminedependent enzymes is assumed to characterize most of the neurodegenerative diseases. Thiamine deficiency (TD) models have been used to produce selective neurodegeneration basically because of the mild impairment of oxidative metabolism. In the present study, we report that TD elicited a significant decrease in voltage-dependent K+membrane conductance in cerebellar granule neurons. We examined the TD effects on delayed rectifier and A-type K+ channels, two well known voltage-activated K+ channels involved in the regulation of action potential firing in cerebellar granule neurons. Current recordings were performed in cultured rat cerebellar granule neurons using the whole-cell voltageclamp technique. TD markedly depressed the transient A-type K+currents. The present results suggest that, by inhibiting IA, there is increase in action potential firing. Both situations could cause neuronal cell death.